1984
DOI: 10.1177/070674378402900104
|View full text |Cite
|
Sign up to set email alerts
|

Grief Reactions to Perinatal Death — a Follow-Up Study

Abstract: Thirty mothers who experienced a perinatal death were offered crisis intervention aimed at facilitating their grief process at a few days, 3 weeks and 3 months after the loss. Evaluation of maternal grief reactions and their general psychological adjustment took place at these 3 early contacts and 1 to 2 years later. This last assessment included a semi-structured clinical interview and a number of self-rating scales (Life Events Schedule, Beck Depression Inventory (BDI) and a Mourning Scale). Six of the 30 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
39
1

Year Published

1989
1989
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 11 publications
2
39
1
Order By: Relevance
“…16,17 Even in highresource settings in which psychological support might be available, one in fi ve mothers has appreciable long-term depression, anxiety, or post-traumatic stress disorder after a stillbirth. [17][18][19] Fathers are also aff ected by negative psychosocial consequences. 20 When compared with the leading global causes of death in all age categories, all-cause stillbirths would rank fi fth among the global health burdens-before diarrhoea, HIV/AIDS, tuberculosis, traffi c accidents, and any form of cancer.…”
Section: Why Stillbirths Mattermentioning
confidence: 99%
“…16,17 Even in highresource settings in which psychological support might be available, one in fi ve mothers has appreciable long-term depression, anxiety, or post-traumatic stress disorder after a stillbirth. [17][18][19] Fathers are also aff ected by negative psychosocial consequences. 20 When compared with the leading global causes of death in all age categories, all-cause stillbirths would rank fi fth among the global health burdens-before diarrhoea, HIV/AIDS, tuberculosis, traffi c accidents, and any form of cancer.…”
Section: Why Stillbirths Mattermentioning
confidence: 99%
“…Neighbors, friends, health care professionals, and even other family members often react inappropriately to the baby's death by either avoiding the parents or the subject or by misplaced cheer, "you're young, you can have other children" (Nichols, 1986 (Giles, 1970;Laroche et al, 1984;Rowe et al, 1978). MaternaI response to these losses, regardless of the cause of death or the age of the infant at the time of death, has been found to be qualitatively similar (Giles, 1970;Laroche et al, 1984;Rcwe et al, 1978). However, with the exception of one study by sociologists Peppers and Knapp (1980), there has not been any systematic research done on the gestational age of the infant as a factor in perinatal grieving.…”
Section: Reviv Ot the Litraturementioning
confidence: 99%
“…Bereaved parents may experience physical symptoms such as fatigue, insomnia, anarexia, irritability, aches, and pains, just ta name a few (Benfield et al, 1978;De Frain & Ernst, 1978;Laroche et al, 1984;Miles, 1985). Changes in behaviour may include inability ta concentrate, ( disorganization, disorientation, confusion of thought processes, and a tendency to either withdraw or to become hyperactive (Miles, 1984).…”
Section: Parental Grief Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…While the presence of other children in the family is positively correlated with lower levels of depression, anxiety, and grief symptoms in some studies (Bennett et al, 2008), other studies showed a negative (La-Roche et al, 1984) or no impact (Swanson et al, 2007).…”
mentioning
confidence: 97%